Efecto del uso de diferentes dosis de Micorrizas arbusculares con distintas frecuencias de aplicación, en el rendimiento de pimiento (Capsicum annuum L.) variedad Iguazú, en el barrio La Vega, cantón Catamayo - Celi Alulima, Bryan German (2022)
The pepper plant (Capsicum annuum L.) plays a very important role in human nutrition, especially in terms of minerals and vitamins. In 2015 and 2017, an average of 2 300 hectares were planted in Ecuador, with a yield of 37 826 kg/ha; therefore, it has been considered one of the most relevant foods, and some outstanding varieties such as red, green and yellow bell pepper are recognized. In Catamayo canton, pepper cultivation is a valuable economic activity for farmers; the plantations are established by small farmers using conventional methods. However, the use of pesticides and inorganic fertilizers in agricultural ecosystems has generated environmental problems, in this sense the microbial component is essential for the balance of ecosystems. In order to increase pepper yield and productivity, mycorrhizae can be used as an environmentally friendly alternative. In the present research, different doses of mycorrhizae applied with three different frequencies to the pepper variety called Iguazú F1, were evaluated under agronomic management in the Catamayo canton. The crop was established in Barrio La Vega, in Catamayo canton, southern Ecuador, with a duration of 5 months, planted at a density of 31 250 plants per hectare, under a completely randomized design (CRD) with bifactorial arrangement (3 doses of mycorrhizae: 0.5, 1 and 2 kg/ha, applied at 3 frequencies: 7, 15 and 30 days) and a total of 12 treatments. Height, stem diameter, leaf area, fresh and dry biomass of the aerial part of the plant, mortality, flowering time, number of flowers and fruit per plant, fruit length, diameter and weight, and yield expressed in t/ha were evaluated. Regarding to vegetative growth, no significant differences were obtained; however, the treatment with 1 kg/ha applied every 30 days stood out in the variable of fresh and dry biomass of the plant and showed better bioprotection against phytopathogenic fungi with 0% mortality. The application of 2 kg/ha of mycorrhizae every 15 and 30 days increased yield by 16.48 t/ha due to the effect on fruit weight. Results of this study show that different doses of mycorrhizae applied at different frequencies can improve yields in bell pepper plantations adapted to the Catamayo canton. Keywords: Pepper, Capsicum annuum, mycorrhizae, Catamayo.